Single-magnon tunneling through a ferromagnetic nanochain - Petrov, E.G.; Ostrovsky, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Magnon transmission between ferromagnetic contacts coupled by a linear ferromagnetic chain is studied atthe condition when the chain exhibits itself as a tunnel magnon transmitter. It is shown that dependently on magnonenergy at the chain, a distant intercontact magnon transmission occurs either in resonant or off-resonanttunneling regime. In the first case, a transmission function depends weakly on the number of chain sites whereasat off-resonant regime the same function manifests an exponential drop with the chain length. Change of directionof external magnetic field in one of ferromagnetic contacts blocks a tunnel transmission of magnon.